Characterization and antivirus activities of a novel bovine IFN-omega24. Issue 2 (August 2015) - Luo, Xiuxin; Guo, Yongli; Bao, Jun; Liu, Ying; An, Dong; Ma, Bo; Gao, Mingchun; Wang, Junwei
Highlights: A novel bovine IFN-ω subtype gene was amplified and named BoIFN-ω24. The recombinant mature peptide was expressed in prokaryotic expression system. BoIFN-ω24 has antiviral activity on MDBK, BT and PK-15 cells. Physicochemical characteristics and antiproliferation of BoIFN-ω24 were determined. Abstract: A novel bovine interferon-ω (BoIFN-ω) gene, which encodes a protein of 195 amino acids with a 23-amino acid signal peptide, was amplified from bovine liver genomic DNA through PCR and named BoIFN-ω24 according to its position in the bovine genome. In this study, the recombinant protein was expressed in Escherichia coli and antiviral or antiproliferation activity was determined in vitro. Results showed that BoIFN-ω24 exhibits high antiviral activity, which can be abrogated using PAb against BoIFN-ω24, and inhibits cell proliferation. BoIFN-ω24 also presents high sensitivity to trypsin and stability at pH 2.0 or 65 °C, which are typical characteristics of type I IFN. This study revealed that BoIFN-ω24 is a potential novel effective therapeutic agent and provided a basis for further research on the BoIFN-ω multigene family.